The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s0102-311x2002000600026
|View full text |Cite
|
Sign up to set email alerts
|

Relações entre saneamento, saúde pública e meio ambiente: elementos para formulação de um modelo de planejamento em saneamento

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
49

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 16 publications
0
7
0
49
Order By: Relevance
“…Such infections may also occur in the domestic environment, where sanitary education, notions of hygiene, and cultural aspects are relevant to the elimination of these diseases. 14 A study investigating the prevalence of intestinal parasitoses among the population of São José da Bela Vista, state of São Paulo, showed that, of 1,032 stool tests, 44.4% had positive outcomes, and that these were associated with low family income and large family size, precarious personal and household hygiene conditions, and poor knowledge concerning the prevention protozoan and helminthic diseases. 16 Hence, population knowledge is one of the factors which may lead to a reduction of the prevalence of intestinal parasitic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such infections may also occur in the domestic environment, where sanitary education, notions of hygiene, and cultural aspects are relevant to the elimination of these diseases. 14 A study investigating the prevalence of intestinal parasitoses among the population of São José da Bela Vista, state of São Paulo, showed that, of 1,032 stool tests, 44.4% had positive outcomes, and that these were associated with low family income and large family size, precarious personal and household hygiene conditions, and poor knowledge concerning the prevention protozoan and helminthic diseases. 16 Hence, population knowledge is one of the factors which may lead to a reduction of the prevalence of intestinal parasitic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The resolution of this problem has been prevented by the high costs involved in improving basic sanitation, as well as by the lack of educational programs capable of achieving community mobilization, which is fundamental for changing habits and beliefs that contribute to the mechanisms of disease transmission, and often play a role in social underdevelopment. 5,6,10,14,16 The present work was aimed at verifying domestic sewage contamination in a river and two of its affluent streams, evaluating basic sanitation conditions, and…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of this issue thus requires focusing attention on health and environmental sector policies as tools for building and consolidating a fair, healthy, and sustainable society. This concern has also oriented the trend towards practices in sanitation that extend beyond the traditional concept to incorporate environmental aspects (from both the physical and biotic environment) into the population's health concerns 29 . Table 1 shows the data for 2013, disaggregated by planning and administrative areas in the city of Rio de Janeiro (some neighborhoods were left out to adjust to the size of the article), according to the percentage of cases in the local population.…”
Section: Olympic Urban Planning In Rio De Janeiromentioning
confidence: 99%
“…Thus, in keeping with the model proposed by Soares et al 29 , it is necessary to probe into Rio de Janeiro's urban planning for a medium and long- term analysis of the impacts of urban interventions on health and include the entire population in this process (which thus far has been segregating and exclusionary.…”
Section: Health and Environment And The Olympic Games Cyclementioning
confidence: 99%
“…As propostas recentes de gestão pública da qualidade dos recursos hídricos 5 reconhecem as evidências científicas de que o comportamento de risco individual em relação ao uso de águas contaminadas é influenciado por restrições socioeconômicas, viés otimista na percepção sobre risco de contaminação 6,7 e baixa efetividade da divulgação puramente quantitativa de estatísti-cas epidemiológicas na promoção de comportamento preventivo 8,9 .…”
Section: Introductionunclassified